Inheritance pattern recognition method of national traditional sports culture in e-commerce platform - Han, Bing; Lin, Yaohui (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
An E-commerce platform is a new network platform in which information push can improve the speed of information analysis. The traditional pattern recognition ability of cultural heritage recognition is poor, and the amount of recognition data is too small. To solve this problem, the e-commerce platform is used to realize the feature recognition of national traditional sports culture. Through the analysis of national culture data, online information feature extraction is completed to identify the lifestyle, religious belief, ethics and festival customs of national traditional sports culture, and determine the inheritance mode of National Traditional Sports culture in the e-commerce platform. The experimental results show that the recognition method of e-commerce platform has strong recognition ability, and can better identify the inheritance pattern